2017
DOI: 10.1088/1361-6439/aa556b
|View full text |Cite
|
Sign up to set email alerts
|

Design, fabrication, and characterization of bridge-type micro-hotplates with an SU-8 supporting layer for a smart gas sensing system

Abstract: In this study, bridge-type micro-hotplates (MHP) with an SU-8 supporting layer were proposed for smart gas sensor applications. The proposed MHP consisted of a heating membrane with an area of 140 µm  ×  140 µm, and a 33 µm-thick SU-8 layer deposited on its bridges. Finite element method based simulation confirmed that the proposed MHP displayed good thermal isolation properties. The proposed MHP was successfully fabricated, and the properties of the MHP were characterized. Current–voltage characteristics reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…Figure 5a shows the current–voltage (IV) characteristics of the heater. In addition, the heater temperature calculated from the heater resistance [28] was plotted on the graph. It was confirmed that the MHP can be heated to approximately 530 °C at 5 V. The heater temperature plotted against the power consumption of the heater is shown in Figure 5b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5a shows the current–voltage (IV) characteristics of the heater. In addition, the heater temperature calculated from the heater resistance [28] was plotted on the graph. It was confirmed that the MHP can be heated to approximately 530 °C at 5 V. The heater temperature plotted against the power consumption of the heater is shown in Figure 5b.…”
Section: Resultsmentioning
confidence: 99%
“…The membrane area was 140 μm × 140 μm, and the effective area of the device including the bridges was approximately 270 μm × 270 μm. The fabrication details of the MHP are described elsewhere [28]. …”
Section: Methodsmentioning
confidence: 99%
“…Efforts are made to improve the mechanical stability of the suspended structure. Iwata et al [ 49 ] has proposed to reinforce the bridges with the thick polymer layer SU-8 due to its extremely low thermal conductivity ( ) compared to silicon, as well as its compatibility with micromachining processes. However, the reinforced layer increases the fabrication complexity, which is why it has not been adopted in other studies so far.…”
Section: Mems Microhotplatementioning
confidence: 99%
“…A Finite Element Method (FEM) electro-thermal simulation is commonly implemented during the microhotplate design process for optimization of the temperature distribution and power consumption. A large variety of commercially available software such as ANSYS [ 49 , 52 , 53 , 54 , 55 , 56 ], COMSOL Multiphysics [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ], ConventorWare [ 64 , 65 ], ISE TCAD [ 66 , 67 , 68 ] and MEMCAD [ 69 ] has been used. Figure 6 shows the temperature distribution of a suspended membrane microhotplate without a gas sensitive layer for a target temperature of 700 °C [ 54 ].…”
Section: Mems Microhotplatementioning
confidence: 99%
See 1 more Smart Citation